Malignant subclone drives metastasis of genetically and phenotypically heterogenous cell clusters through fibrotic niche generation - Sau Yee Kok (Nature Portfolio, 2021)
Cancer cell clusters metastasize to distant organ by polyclonal manner. Here, the authors show that malignant subclone induces fibrotic niche generation in the liver by hepatic stellate cell activation, supporting survival and colonization of non-metastatic cells to develop polyclonal metastasis.